Circumstances of the establishment of the Eastern Main Channel, water utilisation problems and alternatives - Nagy, Sándor (Acta Agraria Debreceniensis, 2012)
After hundreds of years of drought in the area of Hortobágy and its surroundings brought up the idea of building a channel in Tiszántúl. It started with the idea of an irrigation canal but it ended up in a canal with high importance which can be used in many ways. Because of financial problems the necessary renovations cannot be achieved, and as a side effect the amount of silt in the water started to increase, water exploitation started to decrease, and the construction works started to get spoiled. Guided by the Water Directive the East Main Channel has become one of the most significant surface water base in Hungary. To use its water as drinking water brings up a few questions, like solving the pollution problems which problems have already occured. If we want the East Main Channel to be a solution for a long time, further steps and researches are needed to solve the problem of diverting the huge amount of precipitation of the last few years and miantaining the quality of drinking water.